Ukraine's EU Integration: A Long Way Home - Ilona Sologoub (Intereconomics, 2022)
It is time to admit that while Russia remains an empire and has nuclear weapons, it will always be an existential threat to democracies.
Keywords: F15; F51; F55; 330